Mineralocorticoid Antagonist Improves Glucocorticoid Receptor Signaling and Dexamethasone Analgesia in an Animal Model of Low Back Pain - Ibrahim, Shaimaa I. A.; Xie, Wenrui; Strong, Judith A.; Tonello, Raquel; Berta, Temugin; Zhang, Jun-Ming (Frontiers in Cellular Neuroscience, 2018)
Low back pain, a leading cause of disability, is commonly treated by epidural steroid injections that target the anti-inflammatory glucocorticoid receptor (GR). However, their efficacy has been controversial. All currently used epidural steroids also activate the pro-inflammatory mineralocorticoid receptor (MR) with significant potency. Local inflammation of the dorsal root ganglia (DRG), a rat model of low back pain was used. This model causes static and dynamic mechanical allodynia, cold allodynia, and guarding behavior (a measure of spontaneous pain), and activates the MR, with pro-nociceptive effects. In this study, effects of local dexamethasone (a glucocorticoid used in epidural injections), and eplerenone (a second generation, more selective MR antagonist) applied to the DRG at the time of inflammation were examined. Mechanical and spontaneous pain behaviors were more effectively reduced by the combination of dexamethasone and eplerenone than by either alone. The combination of steroids was particularly effective than dexamethasone alone or the model alone (3-fold improvement for mechanical allodynia) at later times (day 14). Immunohistochemical analysis of the GR in the DRG showed that the receptor was expressed in neurons of all size classes, and in non-neuronal cells including satellite glia. The GR immunoreactivity was downregulated by DRG inflammation (48%) starting on day 1, consistent with the reduction of GR (57%) observed by Western blot, when compared to control animals. On day 14, the combination of dexamethasone and eplerenone resulted in rescue of GR immunoreactivity that was not seen with dexamethasone alone. The results suggest that eplerenone may enhance the effectiveness of clinically used epidural steroid injections, in part by enhancing the availability of the GR. Thus, the glucocorticoid-mineralocorticoid interactions may limit the effectiveness of epidural steroids through the regulation of the GR in the dorsal root ganglia.